AB1032 Higher body fat is an independent risk factor for metabolic syndrome in gout. (12th June 2018) - Liang, J.-J.; Ao, S.-T.; Li, Q.-H.; Xu, Y.-H.; Du, X.-Y.; Yang, K.-M.; Lin, J.-Z.; Mo, Y.-Q.; Dai, L.
Abstract : Background: The development of gout is associated with obesity and metabolic syndrome (MS). Obesity is defined by body mass index (BMI). However, BMI has being challenged for the limitation of not distinguishing different comprising tissues of the body. Body composition (BC) has been frequently recommended to assess metabolic status and will eventually replace BMI as a more reliable measure. Objectives: To investigate the characteristics of BC in gout patients and their significance with disease characteristics. Methods: BC was assessed in 180 consecutive gout patients and1, 860 control subjects (white-collar employees in Zhangjiang InnoPark of Shanghai) by bioelectric impedance analysis. Overfat was defined by body fat percentage (BF%) as ≥25% for men and ≥35% for women. Demographic and clinical data as well as comorbid diseases were collected simultaneously. For the significant differences in the proportion of gender and age between two groups, the age- and gender-matched control subjects were randomly selected with the ratio of 1:1 for further statistics. Results: (1)Among 180 gout patients recruited, the mean age was 42.5±15.5 years, mean serum uric acid (sUA) was 9.0±2.4 mg/dl and 17.2% of patients presented tophi. The mean BMI was 25.4±3.5 kg/m 2 with 44.4% overweight and 25.6% obesity. The mean BF was 26.2%±6.6% with 50.5% overfat. (2)Compared with control subjects, gout patients were characterised by higher BMI (25.4±3.5 kg/m 2 vs. 24.3±3.3 kg/m 2 ), fat mass (19.3±6.9 kg vs. 16.5±6.2 kg), trunk fat mass (10.2±5.4 kg vs. 8.4±3.4 kg), BF (26.2%±6.6% vs. 22.4±6.2%), proportion of overfat (50.5% vs. 27.2%), but lower lean mass (53.0±7.7 kg vs. 55.6±7.7 kg, all p<0.05). (3)Compared with normal fat patients (n=89), gout patients with overfat (n=91) presented higher duration of gout, the count of affected joints, flare times in the past year, family history and presence of tophi (all p<0.05, table 1). Overfat gout patients also exhibited higher BMI, more obesity, hyper-low density lipoproteinemia, MS and fatty liver (all p<0.05). (4)There were 9 (17.3%) overfat gout patients in 53 normal weight patients who presented more hypercholesterolemia (55.6% vs. 13.3%), hyper-low density lipoproteinemia (55.6% vs. 17.8%) and fatty liver (77.8% vs. 35.6%) and less skeletal muscle mass index (SMMI, 8.3±0.5 kg/m 2 vs. 9.7±0.7 kg/m 2 ) than those patients with normal fat and weight (all p<0.05). Meanwhile, there were 44 (34.9%) gout patients with normal fat among 126 overweight and obesity patients who had less MS (40.9% vs. 63.4%) and more SMMI (11.1±0.9 kg/m 2 vs. 10.6±1.1 kg/m 2 ) than overfat patients (both p<0.05). (5)Overfat was a risk factor for MS [OR 3.4 (1.8, 6.4), p<0.001] after adjusted by age and gender. Conclusions: Our results indicated higher body fat in gout patients which is an independent risk factor for MS. Acknowledgements: The present study was supported by Guangdong Natural Science Foundation, China (Grant no. 2014 A030310086) to Qian-Hua Li. Disclosure of Interest: None declared